Electrospun Zr-Doped CaO Sorbent for CO2 Capture - Vyacheslav V. Rodaev; Svetlana S. Razlivalova; Alexander I. Tyurin; Vladimir M. Vasyukov (Nanomaterials, 2023)
A Zr-doped CaO sorbent for high-temperature CO2 capture was fabricated using electrospinning. The nanofiber sorbent with an average filament diameter of about 160 nm is characterized by an initial CO2 uptake capacity of 12.1 mmol/g, a specific surface area of 79 m2/g, an indentation Young’s modulus of 520 MPa, and a hardness of 1.6 MPa. After 50 carbonation/decarbonation cycles, the sorbent has a decent CO2 uptake capacity of 9.7 mmol/g due to the uniform distribution of CaZrO3 in the CaO nanofibers to prevent CaO grain growth caused by CaCO3 sintering. It is revealed that the sorbent CO2 uptake capacity decreases both with an increase in the decarbonation temperature and with an increase in the CO2 concentration in the gas flow upon carbonation, where the sorbent CO2 uptake capacity is more sensitive to the decarbonation temperature than to the CO2 concentration in the gaseous stream during carbonation. It is assumed that the electrospun regenerable Zr-doped CaO sorbent is effective for removing CO2 from flue gases.